Comparison of Caudal Versus Transforaminal Epidural Steroid Injection in Post Lumbar Surgery Syndrome After Single-level Discectomy: A Prospective, Randomized Trial - ŞENCAN, SAVAŞ; GÜNDÜZ, OSMAN HAKAN (My University, 2022)
Background: Epidural fibrosis (EF) is one of the leading causes of post lumbar surgery syndrome (PLSS). Although there are studies in the literature suggesting that lumbar epidural steroid injections are an effective method in the pain management of PLSS caused by EF, no study is available comparing the effectiveness and safety of caudal and transforaminal approaches. Objectives: To investigate the efficacy of caudal epidural steroid injection (CESI) versus transforaminal epidural steroid injection (TFESI) in patients with PLSS. Study Design: A prospective, randomized, assessor-blind study. Setting: Interventional pain management center at a tertiary care center. Methods: Patients with low back and radicular pain related to EF following single-level lumbar discectomy were included. The patients were randomly divided into 2 groups: a CESI group and a TFESI group. All patients were assessed before the procedure (baseline) and at one hour, 3 weeks, and 3 months after the procedure using the Numeric Rating Scale (NRS-11) and at baseline, 3 weeks, and 3 months using the modified Oswestry Disability Index (mODI). Treatment success was defined as a ≥ 50% decrease in the NRS-11 scores compared to baseline. Results: A total of 56 patients (n = 26 CESI group; n = 30 TFESI group) were included. NRS-11 and mODI scores showed a significant decline in both groups at all follow-ups (P < 0.001). At 3 weeks, the improvement in the mODI scores was significantly higher in the TFESI group (P = 0.020). In all follow-ups, the NRS-11 scores were similar between the groups. At 3 weeks, the rates of patients with a ≥ 50% decrease in NRS-11 scores were 53.8% and 60% in the CESI group and TFESI group, respectively, while these rates were 30% and 26.7%, respectively, at 3 months. Limitations: This study had no placebo-control group and a relatively short follow-up. Conclusion: Both CESI and TFESI are effective and safe methods in the treatment of PLSS caused by EF following lumbar discectomy. These methods can reduce pain and disability. Although both methods have similar treatment success rates, TFESI seems to be a more effective treatment method in reducing disability at 3-week follow-up. Keywords: Post lumbar surgery syndrome, failed back surgery syndrome, post laminectomy syndrome, epidural fibrosis, epidural steroid injections, transforaminal, caudal, radiculopathy, back pain
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Cerrahi Tıp Bilimleri; Anesteziyoloji; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; Surgery Medicine Sciences; Anesthesiology; ANESTEZİYOLOJİ; Klinik Tıp; Klinik Tıp (MED); KLİNİK NÖROLOJİ; ANESTHESIOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); CLINICAL NEUROLOGY; Neurology (clinical); Anesthesiology and Pain Medicine; Life Sciences; Post lumbar surgery syndrome; failed back surgery syndrome; post laminectomy syndrome; epidural fibrosis; epidural steroid injections; transforaminal; caudal; radiculopathy; back pain; FAILED BACK SURGERY; PERCUTANEOUS ADHESIOLYSIS; CLINICAL EFFECTIVENESS; SPINAL STENOSIS; DISC HERNIATION; RADICULAR PAIN; DOUBLE-BLIND; COMPLICATIONS; MANAGEMENT